Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan di PT Shafira Laras Persada Kota Bandung - Desi Prasetiyani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Employee performance is a critical factor in achieving organizational goals, and it is influenced by various internal and external factors, including motivation and work discipline. In the current competitive business environment, organizations must ensure that their employees maintain high performance levels to sustain productivity and organizational success. PT Shafira Laras Persada, as a growing company, faces challenges in optimizing employee performance, making it necessary to examine the role of motivation and work discipline in shaping employee behavior and productivity. This study aims to analyze the effect of motivation and work discipline on employee performance, both partially and simultaneously, at PT Shafira Laras Persada. The research employed a quantitative approach with an associative method. The population consisted of 65 employees, and the entire population was selected as the research sample using a census technique. Data were collected using closed-ended questionnaires with a Likert scale, distributed directly to the respondents. The collected data were analyzed using SPSS version 27, including descriptive analysis, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that both motivation and work discipline have a positive and significant effect on employee performance. Individually, each factor contributes to improving productivity and work quality. Simultaneously, the combination of motivation and work discipline provides a stronger impact on employee performance, emphasizing the importance of managing these factors together. These findings suggest that the company should strengthen strategies to enhance employee motivation and enforce work discipline to achieve optimal performance and support organizational objectives.